Associations of inflammatory cytokines with palmoplantar pustulosis: a bidirectional Mendelian randomization study - Liu, Chengling; Liu, Xingchen; Xin, Haiming; Li, Xin (Frontiers in Medicine, 2024)
Background Variations in circulatory cytokine levels have been observed during the onset and course of palmoplantar pustulosis (PPP); however, whether these changes are due to etiological or secondary factors is unclear. To clarify the causal relationship, we conducted a summarized-level bidirectional Mendelian randomization (MR) analysis in this study. Methods A FinnGen biobank genome-wide association study (GWAS) of 212,766 individuals (524 PPP patients and 212,242 controls) provided summary data for PPP, whereas genetic instrumental variables (IVs) linked to circulation cytokine levels were gathered from a GWAS of 14,824 European individuals. The inverse-variance weighted (IVW), weighted median (WME), simple mode, and MR-Egger methods were used to ascertain the changes in PPP pathogenic cytokine taxa. Sensitivity analysis, which included horizontal pleiotropy analysis, was then conducted. The reliability of the results was assessed using the leave-one-out approach and the MR Steiger test, which evaluated the strength of a causal relationship. To evaluate the reverse causality between PPP and circulating cytokine levels, a reverse MR analysis was carried out. Results Our study demonstrated positive associations between C-X-C motif chemokine 6 (CXCL6) and PPP (odds ratio, OR 1.257, 95%CI: 1.001–1.570, p = 0.043). C-C motif chemokine 19 (CCL19) and interleukin-6 (IL-6) were suggested to be protectively associated with the development of PPP (OR: 0.698,95% CI: 0.516–0.944, p = 0.020; OR: 0.656, 95%CI:0.437–0.985, p = 0.042). The results were steady after sensitivity and heterogeneity analyses. Conclusion At the genetic prediction level, we identified causally connected inflammation-related variables that contributed to the onset and development of PPP. The therapeutic options for some refractory PPP have expanded due to tailored cytokine therapy, generating fresh concepts for PPP diagnostics and mechanism investigation.